Mealtime Environment and Control of Food Intake in Healthy Children and in Children with Gastrointestinal Diseases - Katerina Sdravou; Elpida Emmanouilidou-Fotoulaki; Athanasia Printza; Elias Andreoulakis; Athanasios Evangeliou; Maria Fotoulaki (MDPI AG, 2021)
Parental feeding practices and mealtime routine significantly influence a child's eating behavior. The aim of this study was to investigate the mealtime environment in healthy children and children with gastrointestinal diseases. We conducted a cross-sectional case-control study among 787 healthy, typically developing children and 141 children with gastrointestinal diseases, aged two to seven years. Parents were asked to provide data on demographics and describe their mealtime environment by answering to 24 closed-ended questions. It was found that the majority of the children had the same number of meals every day and at the same hour. Parents of both groups exerted considerable control on the child's food intake by deciding both when and what their child eats. Almost one third of the parents also decided how much their child eats. The two groups differed significantly in nine of the 24 questions. The study showed that both groups provided structured and consistent mealtime environments. However, a significant proportion of children did not control how much they eat which might impede their ability to self-regulate eating. The presence of a gastrointestinal disease was found to be associated with reduced child autonomy, hampered hunger cues and frequent use of distractions during meals.